Empowering The Quality of Students Publication Through Scientific Writing Training at UIN Imam Bonjol Padang - Fahmi, Reza; Aswirna, Prima; Fahmi, Farah Audi; Fahmi, Danial Muhammad (Proceedings of Annual Conference on Community Engagement, 2022)
This research departs from the fact that many students have difficulty in writing scientific papers. This contributes to delays in completion of studies. The purpose of this research is to provide reinforcement to the writing of scientific papers through scientific writing training. The participants who were involved in this devotional research were 68 people. The results of this study found that the training had succeeded in improving the ability or skills of writing scientific papers. However, training needs to be followed by continuous training activities.